Development and performance of the c4c national clinical trial networks for optimizing pediatric trial facilitation - Degraeuwe, Eva; van der Geest, Tessa; Persijn, Laura; Nuytinck, Lieve; Raes, Ann; Turner, Mark; Fernandes, Ricardo M.; Vande Walle, Johan; de Wildt, Saskia N., IMI2 project conect4children (c4c) consortium, including National Hubs/Networks Belgian Pediatric Clinical Research Network (BPCRN) (Belgium) and Pedmed-NL (Netherlands) (Frontiers in Pediatrics, 2023)
Over the past decade, facilitative networks for pediatric clinical trials have emerged globally, primarily founded by pediatricians with mixed funding sources. These networks aim to increase clinical trial success and ultimately improve the delivery of innovative medicines. Within the European conect4children (c4c) project, national clinical trial networks contribute to efficient trial execution in a centralized way. We show excellent performance metrics of the trial feasibility process by the Belgian and Dutch Networks and present the learnings and challenges encountered, which presents clear guidance for further development of effective pediatric trial networks.